A New Derivation of Extended Watson Summation Theorem with an Application - Paudel, Resham Prasad; Harsh, Harsh Vardan; Poudel, Madhav Prasad; Basnet, Ganesh Bahadur (Journal of Nepal Mathematical Society, 2025)
In this research article, we aim to provide a new proof of the extended Watson summation theorem for the series 4F3 obtained earlier by Kim et al. As an application, we evaluate four interesting integrals involving generalised hypergeometric function.